Social interaction, sense of belonging, and psychological wellbeing: a study of Chinese international students in UK higher education - Zhang, Han; Abbott, Nicola; Waldeck, Daniel; Holliman, Andrew (Frontiers in Education, 2025)
Going to university is a time of great change and adjustment for students, particularly for Chinese international students (CIS) who are crossing borders and cultures to pursue their studies. The existing literature has shown that CIS social interaction is associated with their sense of belonging at university which, in turn, is associated with their psychological wellbeing. However, there remains a paucity of work examining these relationships within a single study, especially among CIS in the United Kingdom (UK), where social interaction, sense of belonging, and psychological wellbeing, are reported to be of concern. In the present study, 85 CIS at UK universities, were surveyed for their social interaction (peer and teacher-student relationships) and sense of belonging at university as well as their psychological wellbeing. It was found that students' social interactions and sense of belonging at university were significantly positively related with psychological wellbeing. Moreover, mediation analyses revealed that sense of belonging at university partially mediated the relationship between peer interactions and psychological wellbeing but fully mediated the relationship between teacher-student interactions and psychological wellbeing. Despite some limitations (e.g., sampling and methodological issues), this study makes a valuable contribution to understanding how different forms of social interactions (e.g., peer and teacher-student) affect CIS students' sense of belonging and, in turn, their psychological wellbeing. It also contributes practically, suggesting that initiatives such as expanded extracurricular opportunities and university peer mentoring programs may foster positive social interactions. These, in turn, may enhance students' sense of belonging at university and their psychological wellbeing.